The application of IoT-based hydroponic system and solar power to increase agricultural production and horticultural crop productivity - Hermala, Irvan; Ismail, Agus; Hendrasto, Nur; Maulida Darda, Azqia; Daulay, Syukur (International Journal of Engineering and Technology, 2022)
Agriculture is important sector to fill the basic need of human: food. It will increase as the increasing of population. In this researh, IoT that was powered by solar power was successfully implemented to hydroponic system. The IoT controlled the parameter and solar panel power in the hydroponic system effectively where the solar panel generated power up to 2.5 kW during the day and it was used for powering greenhouse that need about 477 W power. Research was conducted by comparing productivity of conventional farming to hydroponic smart farming. The physical properties of plants from species of Ipomea aquatica, Brassica chinensi, Lactuca sativa, and Brassica rapa that were cultivated in smart farming and conventional farming were measured and analyzed. It was revealed that the height of Ipomoea aquatica was 52.63 cm in smart farming, whereas the height was 42.66 cm in conventional farming. The average height and weight of the plants and the number of leaves lead to the fact that smart farming results in higher productivity than other method because of optimum nutrition in smart farming.Â Â